Examining issues and challenges in integrating SMEs into global value chains: Malaysia evidence” - Ibrahim, Khairunisah; Abdullah, Moha Asri; Sulaiman, Maliah; Adhiatma, Ardian; Djayusman, Royyan Ramdani (UMY Press, 2020)
Small and medium enterprises (SMEs) are considered as the engine of economic growth as they make a huge portion in the economic pie both in the developed and developing markets and in terms of employment and intergenerational sustainability, as well as economic growth. The develop-ment and growth of SMEs in Malaysia has significant impact in boosting productivity and increasing employment at national, regional and global markets. Increasingly globalized links in production networks or global value chain provide opportunities for SMEs to upscale their business models and to grow across borders. This chapter aims to examine the issues and challenges faced by SMEs in Malaysia in becoming more competitive and expanding their businesses into the international market. The survey was conducted us-ing structured questionnaire that involved two sections of 18 and 16 ques-tions in each section respectively in terms of issues in business and challenges in the global trade market. Data collected from 344 respondents were then analyzed based on descriptive statistics using SPSS software. Findings shows that Malaysian entrepreneurs are highly concerned with the future economic and cost uncertainties as well as the rapid technological changes around the world, including digital economy, e-commerce, and digital trade zone. In competing globally, SMEs in Malaysia are experiencing challenges in having adequate knowledge and information pertaining to international ventures, including knowledge on the international market opportunities, information on the marketing channels and networks, foreign market system as well as adaptation of products to foreign markets. Discrepancies in feedbacks are also identified with regards to the distinct personalities and demographics of the SMEs. This chapter provides crucial information to regulators, policy makers and SMEs in Malaysia in enhancing SMEs participation in the global value chains.